2017
DOI: 10.4081/gc.2017.6377
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and hospitalizations in the elderly

Abstract: Pneumonia in the elderly is a common and severe problem. In this review we analyze the state of the art for pneumonia in the elderly. Several aspects are discussed: i) how common is the disease; signs and symptoms in the elderly; ii) the elderly must always be hospitalized and which is the best place -Intensive Care Unit or medical ward?; iii) the role of comorbidities; iv) etiology and pathogenesis; medical treatment -when and how to start; v) antibiotic resistance; vi) antibiotics in hospital acquired and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Given that majority of elderly patients have multiple co-morbidities that increases their risk for pneumonia, this study showed that most of elderly admitted have diabetes, renal disease, heart failure as well as pulmonary tuberculosis and hypertension similar to other studies [4,12,14,19,[21][22][23]. Among numerous underlying conditions evaluated, the study showed that renal disease has an increased risk for mortality among elderly with community acquired pneumonia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Given that majority of elderly patients have multiple co-morbidities that increases their risk for pneumonia, this study showed that most of elderly admitted have diabetes, renal disease, heart failure as well as pulmonary tuberculosis and hypertension similar to other studies [4,12,14,19,[21][22][23]. Among numerous underlying conditions evaluated, the study showed that renal disease has an increased risk for mortality among elderly with community acquired pneumonia.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical manifestations of elderly with pneumonia stated in various literature were not limited to respiratory symptoms but usually presented with atypical symptoms such as body weakness, changes in sensorium, loss of appetite and can significantly increase the risk of mortality among elderly [8][9]16,22,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…showed higher incidence of Pneumonia in geriatrics when compared to all other RTIs. The study showed 25-44 per 1000 cases with an incidence of Community Acquired Pneumonia 16 .…”
Section: Discussionmentioning
confidence: 85%
“…Cacciatore et al (2017) presented analysis of Italian cases of pneumonia observed in elderly [ 92 ] before COVID-19 was discovered. The data of this study are suitable for comparison with pneumonia associated with COVID-19 positivity.…”
Section: Resultsmentioning
confidence: 99%
“…Several aspects are discussed: 1) how common is the disease; signs and symptoms in the elderly; 2) the elderly must always be hospitalized and which is the best place - ICU or medical ward? ; 3) the role of comorbidities; 4) etiology and pathogenesis; medical treatment - when and how to start; 5) antibiotic resistance; 6) antibiotics in hospital-acquired and ventilator-related pneumonia; 7) assisted non-invasive ventilation; 8) the treatment in the terminally ill elderly patient [ 92 ]. Pneumonia is a frequent illness highly conditioning morbidity and mortality in the elderly population.…”
Section: Resultsmentioning
confidence: 99%